Um passado presente no Nordeste do Brasil : a história no cinema contemporâneo - Freire, Keline Pereira (2020)
This work proposes an analysis that includes fictional feature films produced on the Nordeste between 1995 and 2018. The focus is on films that approach the region from a critical remembrance of history. Based on the concept of history and notions of Rememoration, Cultural Transmission and Regeneration, proposed by Benjamin (1987), we turn to analyze the achievements that we consider promoting a critical remembrance of the national past. From the methodological paths proposed by the comparative cinema, present in the works of Xavier (1983), Souto (2016 and 2017) and Mesquita (2018), we report to the films seeking to build a collection of works that are similar in the sense of establishing a non-conformist remembrance of history. Recognizing similarities and differences, we see in this contemporary filmography the repetition of themes, such as: colonialism, cangaço, sertão, dictatorship, subjective experience in urban space. From this production of Retomada (1995-2003) and Post-retake (2003- present days) it was possible to identify thematic subgroups: The Brazilian colonial past and its implications in the present; The cangaço revisited; The contemporary hinterland and the untold stories; Between pain and affection: cinema and the production of memory about the military dictatorship; The limits between the rural and the urban, the past and the present. We observed that these achievements present lines of flight in the representation of the historical themes they address. They both help us to think of the Nordeste far from stereotyped representations, but also promote a broader debate about Brazil and its historical problems of the past and the present. We understand that this historical discourse, less naturalistic and more critical about the country, is evidenced in the films from the encounter between past and present that they promote, which indicates the look of these works on history without losing sight of the events of the contemporary present. The approach to history in these films, therefore, meets Benjamin definitions of history, since they rescue the past in order to elucidate the oppressions suffered by the subordinate classes, alerting for the continuation of these oppressions in the present. However, with regard to regeneration, indicated by the German author as a state after remembrance, we still consider it to be far from reaching.